Advancements and Innovations in Marine Fuel Technology - Liu Yimeng (E3S Web of Conferences)
This paper provides a comprehensive overview of the application of three clean energy engines— Liquefied Natural Gas (LNG), hydrogen, and ammonia— in the shipping industry. The shipping industry is increasingly exploring clean energy alternatives to reduce its carbon footprint. LNG is one of the most established and widely adopted options, owing to its mature technology and reduced emissions compared to conventional fuels. However, it remains a non-renewable resource and still produces some pollution, making it a less-than-ideal solution for long-term sustainability. Hydrogen, with its high combustion efficiency and zero direct emissions, holds promise as a truly clean fuel. Nonetheless, it faces significant obstacles, including high costs related to production, storage, and transportation, as well as safety concerns due to hydrogen embrittlement and flammability. Ammonia offers the potential for zero-carbon emissions and can be produced using renewable energy sources. Yet, its use is limited by poor combustion characteristics and high corrosiveness, which pose challenges for engine design and material durability. This article delves into the advantages and limitations of these three fuels, focusing on aspects such as corrosion resistance, transportation logistics, pollution levels, friction reduction, and combustion efficiency. The paper concludes by examining future development directions for each energy source within the maritime sector, highlighting the importance of continued innovation to achieve sustainable shipping practices.